The loss of large wood affects rocky mountain trout populations. Issue 4 (15th July 2018) - Herdrich, Adam T.; Winkelman, Dana L.; Venarsky, Michael P.; Walters, David M.; Wohl, Ellen
Abstract: Western U.S. rivers are currently influenced by legacy effects of reduced large wood (LW) loading and retention that has substantially reduced in‐stream habitat complexity. Large wood is typically associated with streams in undisturbed old‐growth forest and in the correct geomorphic context can drastically alter stream and valley habitat complexity. Streams with LW are typically multichannel and depositional, while streams lacking LW, due to relatively recent wildfire or logging (<200 years ago), are usually single channelled and erosional. We compared population biomass and individual growth rates of Brook Trout Salvelinus fontinalis in streams across a gradient of wood volumes. At both the square metre and valley length scales, standing stock biomass of aquatic invertebrates was the best predictor of trout biomass. However, at the valley scale, the number of pools was important in predicting trout biomass in combination with standing stock biomass of aquatic invertebrates. Individual growth rates of age‐1 Brook Trout were negatively affected by increasing density; however, growth rates for the largest and smallest individuals at each site were unaffected by density. Our results suggest the pool habitat created by LW acts synergistically with prey availability to dramatically increase trout populations. However, in streams lacking LW, negative effects of detrimental land use practices have persisted >100 years, suggesting that recovering lost animal production in mountain stream networks will only occur at decadal to century time scales.